2018
DOI: 10.1111/cea.13100
|View full text |Cite
|
Sign up to set email alerts
|

Birth order and paediatric allergic disease: A nationwide longitudinal survey

Abstract: The influence of birth order depended on the type of allergic disease and the childhood period. Childhood is unique in terms of physical and immunological development, and the immune response to the post-natal environment in childhood appears to be heterogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The noted positive associations between adiposity, cesarean delivery, and parental history of FA and the prevalence of study-defined FA are consistent with the findings of prior investigations 53, 54, 55. Similarly, the observed inverse association between birth order and the prevalence of study-defined FA is consistent with the findings of prior studies 4, 56. Although emerging evidence suggests that exposure to dogs in early life reduces the risk of FA,4, 52 our study showed that exposure to dogs in infancy was associated with an increased prevalence of study-defined FA, an association that needs further corroboration.…”
Section: Discussionsupporting
confidence: 88%
“…The noted positive associations between adiposity, cesarean delivery, and parental history of FA and the prevalence of study-defined FA are consistent with the findings of prior investigations 53, 54, 55. Similarly, the observed inverse association between birth order and the prevalence of study-defined FA is consistent with the findings of prior studies 4, 56. Although emerging evidence suggests that exposure to dogs in early life reduces the risk of FA,4, 52 our study showed that exposure to dogs in infancy was associated with an increased prevalence of study-defined FA, an association that needs further corroboration.…”
Section: Discussionsupporting
confidence: 88%
“…The severity of AD has been associated with reduced levels of serum nutrients, such as omega-3 and -6 fatty acids, calcium, folate and vitamin D (29, 30) as well as a higher body mass index (31); while supplementation with a concoction of prebiotics and probiotics showed a significant improvement of AD, particularly among children with more severe AD forms (32). Furthermore, immune response to biological agents, such as S. aureus, has recently been indicated to influence the severity of AD (33), while higher levels of house dust mites have been reported to correlate with more severe AD in children (34). Thus, severe and persistent childhood AD, that represents a risk factor for the development of atopic comorbidities, such as allergic rhinitis or asthma, seems to be the result of complex interplay of genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen covariates were a priori selected based for their potential impact on severe asthma from the data reported in literature: (15,16,31) Lifestyle factors (1 factor) : smoking (never vs. ever) (21,22,32) Early-life factors (6 factors): growing in countryside/farm (33), parental smoking (34), parental asthma and/or allergy (35), severe childhood infections (pneumonia before or during school age or hospitalization due to infection at ≤3 years of age) (36), number of siblings (<2 vs. ≥ 2) (24), birth order (1st vs. other) (24,37,38) Asthma characteristics (1 factor): non-steroidal anti-in ammatory drug (NSAID) -exacerbated respiratory disease (NERD) (17) Chronic comorbidities (3 factors): ≥1 other allergic disease ever [e.g. allergic rhinitis (AR)/allergic conjunctivitis (AC)/atopic dermatitis (AD)] (16,24), nasal polyps (NP) (18), ≥1 other chronic disease(s) (7,21,32).…”
Section: Covariatesmentioning
confidence: 99%